Voices of African immigrants in Kentucky : migration, identity, and transnationality - Musoni, Francis; Otieno, Iddah Aoko; Wilson, Angene Hopkins; Wilson, Jack, 1939- (Kentucky remembered: an oral history series, 2019)
"For centuries, immigration has been a topic of major concern in the US and has seen many significant shifts in policy, particularly within the last 150 years. In the late nineteenth and early twentieth centuries, immigration policy focused on restricting people originating from China. Then, after the passage of the Emergency Quota Act in 1921, quotas for different nations based on existing populations in the country were introduced. In 1965, the US abolished the quota act in favor of a family-based immigration regime. Near the end of the 20th century, immigration policy became preoccupied with the control of "illegal immigrants" mainly from Mexico and Latin American countries. After the 9/11 attacks in 2001, the fight against terrorism became a major part of the immigration debate. Taking into account the most recent immigration bans and President Donald Trump's pledges to build a wall on the US/Mexican border, immigration policy is again an urgent political and social issue. While much attention has been paid to refugees and immigrants from Mexico, Latin America, the Middle East, and Asian countries, very little attention has been given to African immigrants in the US after the Civil War-even though the number of African immigrants living in America has significantly increased over the years. By 2015, more than two million African immigrants were living in the US. Kentucky, in particular, has seen a large increase in African immigrants and refugees since the 1990s, with the population growing from 1,000 to nearly 20,000 residents. The existence of several refugee resettlement agencies and other non-governmental and state sponsored programs, such as Global Lex and the Kentucky Refugee Ministries, make Kentucky a welcoming state for immigrants, and many migrate to the state for educational opportunities. In Voices of African Immigrants in Kentucky, authors Angene and Jack Wilson in conjunction with Iddah Otieno and Francis Musoni, scholars from Kenya and Zimbabwe, challenge scholars and policy makers to broaden their understanding of the diversity of immigration issues in the US. This book, almost entirely based upon one-on-one interviews, provides a historical and theoretical overview of African immigrants in Kentucky, descriptions of their life in home countries, why and how they came to the Bluegrass state-whether it was voluntary or forced-and how they identify themselves and remain in contact with Africa. The book also details the struggles of being an immigrant in Kentucky, challenges that include cultural differences, language barriers, work, and discrimination. Conversely, the narrative also details the positive experiences such as education and job opportunities. Voices of African Immigrants in Kentucky includes stories of next generation African immigrants-young people who were either born in or came to America at a very young age-about their outlook on growing up in the US. By focusing on a less well known immigrant group, the authors spread an understanding of immigration patterns, experiences, and processes in Kentucky"--